An example of identification of thermal behavior of a characteristic machine tool support structure - Pejović, Branko; Gatalo, Ratko (Journal of Production Engineering, 1994)
The paper presents a model of developed software for estimation of thermal behaviour of machine tools support structure in non-stationary cases, which allows behaviour analysis of various construction solutions. Temperatures and temperature displacements were estimated as main thermal characteristics by use of finite elements method. A part of estimation and analysis results from a case study of specific machine tool spindle-arrangement is presented Power generated by friction in the main spindle bearings was adopted as main heat source with invariable intensity. Also considered was a heat-sink effect produced by lubrication and cooling of given bearings. In definition of basic differential equation for heat transmission, all boundary conditions were reduced to boundary conditions of the second type. Regardless of certain deviations between analytical and numerical experimental results, the proposed method is applicable to various kinds of comparisons (for varying geometrical shapes, materials and heat loads) in thermal estimation of elements of machine-tool support structure. The designer is thus given opportunity; well in the design stage, to foresee the behaviour of machine tool structure in exploitation.